Arranged Marriage to Enforced Women’s Objectification in Blue-Winged Girls by Husn Tabassum Nihan - Destinalutfi Citra Rahmadani; Muhammad Faisal Raihan Mulya Fernandi; Satya Bagaskara Saputra (Morphosis: Journal of Literature, 2024)
This Research examines the short story Blue-Winged Girls by Husn Tabassum Nihan which portrays the journey of the Indian women, Razia, Rani, and Sheeba in navigating societal expectations and cultural constraints within an arranged marriage context. The method used in this research is a descriptive qualitative research method in conducting this research by collecting data through the story. The theory utilized in this research is the theory of feminism proposed by Simone De Beauvoir in her book The Second Sex. Drawing upon those theories, in the short story Blue-Winged Girls, Husn Tabassum Nihan conveyed that the struggle for women’s rights was an important part of the larger struggle for Indian women. Razia, Rani, and Sheeba, in this story, try to show that women have the right to marry someone they love and regardless of caste.